Lightning Injury (Bangladesh Critical Care Journal, 2017)
Lightning injuries are injuries caused by lightning strikes. Lightning delivers a massive electrical pulse over a fraction of a millisecond. It can kill a person by instantaneously short-circuiting the heart. Lightning injuries have been the second most common cause of storm-related death in the United States1,2,3. Far more injuries and deaths occur in tropical and subtropical countries. Here we present the case report of a 45 year old Bangladeshi lady who was struck by lightning. Patient presented with immediate loss of consciousness and some superficial skin burn about 1 hour following the event. Over the next few days she was found to have intracerebral haemorrhage and infarct, tympanic membrane rupture and bilateral cataract. Surprisingly patient did not suffer from any cardiac or renal injury. All lightning strike victims should receive emergency medical support on site of injury and be treated in intensive care units (ICU) equipped with multiple organ support facility.Bangladesh Crit Care J September 2017; 5(2): 132-134